Low Expression of S100P Is Associated With Poor Prognosis in Patients With Clear Cell Adenocarcinoma of the Ovary. Issue 9 (1st November 2015) - Umezaki, Yasushi; Ito, Masahiro; Nakashima, Masahiro; Mihara, Yumi; Kurohama, Hirokazu; Yatsunami, Naoko; Yasuhi, Ichiro
Abstract : Objective: The S100P protein stimulates cell proliferation and survival, thereby contributing to cancer progression. The purposes of this study were to evaluate S100P expression in ovarian clear cell adenocarcinoma and to determine whether S100P expression was correlated with the clinicopathological features or prognoses of patients with clear cell adenocarcinoma. Methods: We examined S100P expression in 30 ovarian clear cell adenocarcinoma specimens using immunohistochemistry analysis. The Kaplan-Meier method was used for analysis of overall survival, and comparisons were made based on the log-rank test. Results: Negative staining for nuclear S100P was associated with a poor prognosis as compared with that of positive staining for nuclear S100P in specimens from patients with clear cell adenocarcinoma. Conclusions: These data suggested that S100P may serve as an independent prognostic factor and marker for acquired resistance to chemotherapeutic drugs in clear cell adenocarcinoma.